Determination of Frying Temperature and Vacuum Pressure to Produce Pineapple Chips Using Simple Vacuum Fryer - Yuniarti, Yuniarti; W., Susinggih; Hidayat, Nur; Lastriyanto, Anang (Jurnal Teknologi Pertanian, 2003)
Pineapple is a very cheap fruit and easily to be found throughout the year in Indonesia. Fruit processed as crispy chips is mostly prefered by the consumers. Jackfruit and pineapple crispy chips are popular processed fruit in East Java. These two kinds of fruit have high reducing sugar, so that they must be fried by vacuum frier. For this time being, simple vacuum frier have been successfully produced by some local workshops in relatively cheap price. It is a benefit for the farmers and home industry owners to increase the added value of pineapple fruits. Unfortunately, the proper technology for producing pineapple chips using this simple frier is still unknown. The aim of this research was to determine the frying oil temperature and vacuum pressure of the simple frier used to produce qualified pineapple chips which was prefered by the consumers. Research was designed in a factorial randomized block with the first factor frying temperature 1. e. 1)90 Â°C, 2)l 00 Â°C and 3)110Â°C, while the second factor was vacuum pressure of the fryer 1. e. 1) â500 mm Hg, 2) â600 mm Hg and 3) â700 mm Hg, replicated 3 times. Pineapple variety used was Queen, harvested at farmers orchard in Kedawung, Blitar regency, East Java at 70â80% ripe. Each combination treatment used 3 kg of fruit flesh slices of 2 cm x 2 cm on 2 mm thickness. Total fruit flesh needed was 81 kg. Observation was done on water, reducing sugar and starch content of the chips produced. Preference test was done using hedonic scale scoring to evaluate preferences consumer to the crispiness, colour, taste and flavour of the product. Collected data was then analyzed using LSD test. Result showed that the best temperature for frying oil was 90Â°C, while the best vacuum pressure for frier was â700 mm Hg. Using this method, pineapple chips which were produced had water content 4.85%, reducing sugar content 20.52% and starch content 4.22%. Scores result for preference test were 5.7 (like) for crispiness, 6.20 (like) for colour, 5.60 (like) for taste and 6.30 (like) for flavour. Â  Keywords: Pineapple, simple vacuumfrier, frying temperature, vacuum pressure.